2003
DOI: 10.1186/1475-2891-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and Vitamin E in Prevention of Nonalcoholic Fatty Liver Disease (NAFLD) in Choline Deficient Diet Fed Rats

Abstract: Aim: Oxidative stress has been implicated in the pathogenesis of Nonalcoholic Fatty Liver Disease (NAFLD). Vitamin C and vitamin E are known to react with reactive oxygen species (ROS) blocking the propagation of radical reactions in a wide range of oxidative stress situations. The potential therapeutic efficacy of antioxidants in NAFLD is unknown. The aim of this study was to evaluate the role of antioxidant drugs (vitamin C or vitamin E) in its prevention.Methods: Fatty liver disease was induced in Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 22 publications
6
54
1
1
Order By: Relevance
“…The tissue concentration of these antioxidants is a good indicator of oxidative stress. The clear inverse association between the oxidative stress during liver injury and levels of these antioxidants were well documented and the decreased values of these vitamins in this study is clearly in accordance with previous findings (Krishnamoorthi & Sangeetha, 2008;Oliveira et al, 2003;Saraswathy et al, 2010). Lycopene pretreatment restores the altered levels of these vitamins during D-GalN/LPS toxicity through its antioxidant defense.…”
Section: Discussionsupporting
confidence: 82%
“…The tissue concentration of these antioxidants is a good indicator of oxidative stress. The clear inverse association between the oxidative stress during liver injury and levels of these antioxidants were well documented and the decreased values of these vitamins in this study is clearly in accordance with previous findings (Krishnamoorthi & Sangeetha, 2008;Oliveira et al, 2003;Saraswathy et al, 2010). Lycopene pretreatment restores the altered levels of these vitamins during D-GalN/LPS toxicity through its antioxidant defense.…”
Section: Discussionsupporting
confidence: 82%
“…Drug-induced fatty liver has increased lipid peroxidation (17) and ob/ob mice have an increased ROS production (11). Our group has demonstrated in previous studies that the presence of steatosis correlates with an increase in superoxide anion hydroperoxide generation in animals fed a choline-deficient diet (18) and the use of vitamin C reduces liver steatosis and peroxidation (19). In the present study, lipid peroxidation was also increased and GSH was decreased in the CD group while the oxidative stress of animals fed a high-fat diet enriched with PUFAs-ω-3 was similar to that observed in controls.…”
Section: Discussionmentioning
confidence: 93%
“…A study has shown that vitamin C reduced oxidative stress and markedly inhibited the development of experimental liver steatosis induced by a choline-deficient diet but vitamin E neither prevented the development of fatty liver nor reduced the oxidative stress in this model [26].…”
Section: Experimental Groupsmentioning
confidence: 99%